Travel as Education: Gulliver the Traveller and the Potential Corruptions of Seeking Betterment Abroad - Gill, Dónal (Lumen, 2020)
Travel provides countless opportunities for wonder. The breadth of human experience enabled by traversing new territory includes curiosity, excitement, and surprise. However, achieving this breadth may well be better left unfulfilled. Gulliver’s interactions with the King of Brobdingnag in Book II of Gulliver’s Travels (1726) raise interesting questions regarding travel and its effects on the traveller. This essay argues that Gulliver’s Travels draws upon Locke’s insights into travel as an endeavour with the potential to be didactic, ultimately presenting a case against the universal benefit of embarking on a voyage. Swift’s text offers little hope for the existence of the type of traveller who would be improved rather than corrupted by the experience, which suggests that wonders of travel ought to be avoided. This generates a counter-Enlightenment riposte to liberal assumptions concerning the possibility and likelihood of individual edification through pursuing the wonders of travel.